The Methodology in Islamic Legal Ruling of The Religious Extremism Groups - Abd Razak, Muhd Imran; Ramli, Mohd Anuar; Abdul Rahim, Rahimin Affandi; Yusof @Salleh, Muhammad Yusri; Hassan, Paiz; Zainal Abidin, Mohd Zahirwan Halim (Idealogy Journal, 2018)
Religious extremism is known to take a hard-line on defining religion. This interpretation has resulted in conflicts and tension in the Islamic society. For example, the tendency of takfir makes husband and wife relationships invalid, and even legitimising the blood of other parties. This ideology is perilous, especially in the context of plural society in Malaysia. In this regard, this study discusses the methodology of religious extremism groups in the Islamic legal ruling. To achieve this objective, this qualitative study fully employed the literature review methodology to collect articles for the review. Then, the content is analysed deductively to formulate the findings. The results of the study found that the religious extremists applied a literalist approach, and the nature of their verdict on laws tend to be punitive. Keywords: Religious extremism, takfir, Islamic law, literalism, wasatiyyah